Blackboards and bootstraps revisioning education and schooling - Hamilton, David 1943-; Zufiaurre Goikoetxea, Benjamin (Sense Publ., 2014)
"In drawing a distinction between education and schooling, [this book] identifies, recovers and explores many ideas about education and schooling that are no less important to the practice of the present day than than they were to the pedagogues of the past"--Back cover